2016
DOI: 10.1016/j.jtcvs.2016.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anatomic characteristics and initial biventricular surgical strategy on outcomes in various forms of double-outlet right ventricle

Abstract: Those with the anatomic type of double-outlet right ventricle with noncommitted ventricular septal defect were at higher risk for reoperation and mortality. Intraventricular baffle repair with arterial switch operation was the surgical strategy in patients at higher risk of early death. Initial surgical strategy did not influence the late outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…It can exist as a single malformation or as part of other complex cardiac malformations, such as tetralogy of fallot, complete atrioventricular malformation, transposition of the great arteries, tricuspid atresia, and double outlet of the right ventricle. The location, size and shape of aortic valve orifice and VSD are the key to preoperative preparation (Villemain et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It can exist as a single malformation or as part of other complex cardiac malformations, such as tetralogy of fallot, complete atrioventricular malformation, transposition of the great arteries, tricuspid atresia, and double outlet of the right ventricle. The location, size and shape of aortic valve orifice and VSD are the key to preoperative preparation (Villemain et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Correction of VSD type DORV is not difficult when an intracardiac channel procedure is performed, with generally good results. [ 9 ] In infants <1 year old, however, we found that residual shunts could be inadvertently created in the intracardiac channel, especially for DORV with remote VSD. This could be owing to more difficult exposure of the surgical field, myocardial fragility, and difficulty in suturing.…”
Section: Discussionmentioning
confidence: 90%
“…Four types of DORV (tetralogy of Fallot [TOF] type, transposition of the great arteries [TGAs] type, ventricular septal defect [VSD] type, and remote VSD type) have been classified, and different procedures described for the different types of DORV, with varied rates of success and frequently high mortality. [ 3 4 5 6 7 8 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…1 Em presença de CIV não relacionada como no caso em exposição, a técnica idealizada por Barbero-Marcial 3 direciona o VE para a aorta com tunelização com remendos desde a CIV até a valva aórtica, e com alívio da estenose pulmonar aplicada com relativo sucesso em face de sobrevida de 86,5% após 10 anos. 4,5 Outra técnica, como o direcionamento pela CIV à artéria pulmonar e troca arterial subsequente, também se torna viável.…”
Section: Referênciasunclassified